2002
DOI: 10.1128/jb.184.8.2300-2304.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Zn(II)-Free Treponema pallidum TroA, a Periplasmic Metal-Binding Protein, Reveals a Closed Conformation

Abstract: We previously demonstrated that Treponema pallidum TroA is a periplasmic metal-binding protein (MBP) with a distinctive alpha-helical backbone. To better understand the mechanisms of metal binding and release by TroA, we determined the crystal structure of the apoprotein at a resolution of 2.5 Å and compared it to that of the Zn(II)-bound form (Protein Data Bank accession code 1toa). apo-TroA shows a conformation even more closed than that of its Zn(II)-bound counterpart due to a 4°tilt of the C-terminal domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
86
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 23 publications
6
86
0
1
Order By: Relevance
“…This structure is thought to result in an inability of these proteins to undergo large scale conformational changes upon ligand binding. Indeed, high resolution structures of E. coli BtuF and Treponema pallidum TroA, in both the liganded and unliganded forms, indicate this is to be the case (32)(33)(34). Our results indicate that, in solution, both FhuD1 and FhuD2 from S. aureus do not demonstrate a ligand-induced, large scale conformational change, in agreement with high resolution crystal structures of other members of this binding protein family.…”
Section: Fhud1 In S Aureussupporting
confidence: 73%
“…This structure is thought to result in an inability of these proteins to undergo large scale conformational changes upon ligand binding. Indeed, high resolution structures of E. coli BtuF and Treponema pallidum TroA, in both the liganded and unliganded forms, indicate this is to be the case (32)(33)(34). Our results indicate that, in solution, both FhuD1 and FhuD2 from S. aureus do not demonstrate a ligand-induced, large scale conformational change, in agreement with high resolution crystal structures of other members of this binding protein family.…”
Section: Fhud1 In S Aureussupporting
confidence: 73%
“…2. This rotation is quite modest compared with other PBPs but much larger than the 4°o bserved in the case of the zinc-binding protein TroA (25,26). The hinge motion in NikA is similar to those in OppA and DppA but smaller (30,48).…”
Section: Resultsmentioning
confidence: 73%
“…Unlike the ␤ strands, which connect the lobes of most solute-binding proteins, the helix is rigid and permits only a very small conformational change on ligand binding. It has been suggested that this is necessary for tight metal binding given the small ligand size (26). The crystal structure of a molybdate-binding protein from Azotobacter vinelandii, however, shows a more usual topology with a flexible hinge (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6803 MntC (Syn-MntC) [12], and Eco-ZnuA [13,14] as well as the metal-free (apo) structures of Tpa-TroA [15] and mutant Syn-ZnuA (without the His-rich loop) [8] have been determined by X-ray crystallography. The overall architecture of these MBRs is similar to that of other PLBPs from ABC transporter systems.…”
Section: Introductionmentioning
confidence: 99%